2020
DOI: 10.1101/2020.06.20.20136226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Space-time conditional autoregressive modeling to estimate neighborhood-level risks for dengue fever in Cali, Colombia

Abstract: Vector-borne diseases (VBDs) affect more than 1 billion people a year worldwide, cause over 1 million deaths, and cost hundreds of billions of dollars in societal costs. Mosquitoes are the most common vectors, responsible for transmitting a variety of arboviruses. Dengue fever (DENF) has been responsible for nearly 400 million infections annually. Dengue fever is primarily transmitted by female Aedes aegypti and Aedes albopictus mosquitoes. Since both Aedes species are peri-domestic and container-breeding … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…More than half of the studies (n = 98, 53.6%) included temperature as a covariate while around 40% of studies had rainfall (n = 79, 43.2%). Temperature and rainfall were better fit when lagged one or two months rather than unlagged [38][39][40][41]. Temperature and rainfall were considered as significant factors in most studies, but some studies showed that meteorological factors alone are not sufficient to explain spatial heterogeneity in disease transmission, which may be associated more with non-climatic factors [42][43][44].…”
Section: Spatiotemporal Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…More than half of the studies (n = 98, 53.6%) included temperature as a covariate while around 40% of studies had rainfall (n = 79, 43.2%). Temperature and rainfall were better fit when lagged one or two months rather than unlagged [38][39][40][41]. Temperature and rainfall were considered as significant factors in most studies, but some studies showed that meteorological factors alone are not sufficient to explain spatial heterogeneity in disease transmission, which may be associated more with non-climatic factors [42][43][44].…”
Section: Spatiotemporal Incidencementioning
confidence: 99%
“…For the 33 studies that both checked the multicollinearity of covariates and performed variable selection, we summarised the retention rate of different groups of covariates in the final models (Fig 6A) [27,32,[38][39][40][41][42][43][44][46][47][48]54,59,60,72,78,79,86,93,[99][100][101][102][103][104][105][106][107][108][109][110][111][112]. Of 33 studies, 25 studies (96.2%) retained climatic variables when tested.…”
Section: Spatiotemporal Incidencementioning
confidence: 99%
See 1 more Smart Citation